COLLABORATION OF DEVELOPMENT ACTORS IN REALIZING MANDIRI VILLAGES IN BONGKI LENGKESE VILLAGE, EAST SINJAI DISTRICT, SINJAI DISTRICT - Riskasari, Riskasari; Tahir, Nurbiah (Program Pascasarjana Universitas Negeri Makassar, 2018)
This study aims to find out how the collaboration between Development Actors in realizing Mandiri Village in Bongki Lengkese Village, East Sinjai District, Sinjai District. The realization of Mandiri Village is inseparable from collaborative and balanced collaboration between development actors, namely (Village Government, Community and Business Groups) in the village. This study uses a qualitative approach, with a case study method, for the purposes of collecting data, the researcher conducts observations and in-depth interviews. The results of this study indicate that the collaboration of development actors in Bongki Lengkese Village shows social security in the form of mutual cooperation that is still well preserved by the community, although it has not shown results in economic resilience, especially self-sufficient food for some people, as well as electrical energy etc. Nonetheless, over the past few years it has demonstrated the efforts of development actors in taking on the role as economic drivers of the local community. This is evidenced by the development of a Joint Business Group (KUB) in the form of Goat KUB, Melati KUB, Cow and Blacksmith Fattening, Horti Farmer Group development in this case an increase in chilli production even though the development of Food Farmers Group has not shown optimal results.